(untitled) (Global Journal of Human-Social Science, 2025)
The current economic context is characterized by rapid transformations driven by capitalism, resulting in significant technological advancements and innovations. In this scenario, new concerns and demands arise, such as the pursuit of socio-environmental sustainability and the need to address social inequality, which directly influence entrepreneurship. While these challenges are often seen as obstacles to business profitability, sustainable entrepreneurship emerges as a relevant strategic approach, enabling organizations to adapt and thrive in the era of disruption. In exploring this issue, the following research question arises: How can sustainable entrepreneurship become a facilitating issue for the global leaders in a disruptive environment? It is a descriptive, bibliographic research, qualitative approach, and secondary data source collection. The main research results point that sustainable entrepreneurship: (i) emphasizes innovation and the pursuit of creative solutions for social and environmental challenges; (ii) can provide direct benefits to society, such as improved working conditions and promotion of social equity; (iii) can offer a competitive advantage to entrepreneurs. Thus, this study contributes to understanding the strategies that entrepreneurs can adopt to face challenges and promote sustainable competitiveness.